Pengujian Pengalaman Pengguna Platform LMS Menggunakan Metode UEQ pada Siswa SMP - Alfin Maulid; Rio Setiawan; Ridian Gusdiana (TIN: Terapan Informatika Nusantara, 2026)
The implementation of Learning Management Systems (LMS) in rural Junior High Schools (SMP) faces environmental technical challenges and user oversights (human error). At SMP Negeri 2 Cikajang, the use of LMS for the Summative End-of-Semester Assessment (PSAS) is confronted with fluctuating internet connectivity and student login issues. The urgency of this study lies in the need for an evaluation using the User Experience Questionnaire (UEQ) method to diagnose the multidimensional impact of these technical issues, capturing both pragmatic quality and hedonic quality. This quantitative survey research aims to measure the user experience of the LMS using the UEQ method and to generate adaptive system workflow recommendations. From a population of 932 students, the sample was calculated using the Slovin formula and selected through Proportionate Stratified Random Sampling to ensure representativeness across grade levels (VII, VIII, IX), yielding 95 valid respondents. Data analysis using the UEQ Data Analysis Tool measured six main scales: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The analysis results show exceptionally high mean scores across all dimensions (> 0.8): Attractiveness (2.34), Perspicuity (2.29), Efficiency (2.13), Dependability (1.95), Stimulation (2.24), and Novelty (2.11). Based on the global benchmark analysis, all six dimensions are categorized as Excellent. This study contributes empirically to the evaluation of LMS user experience in rural junior high schools using the User Experience Questionnaire (UEQ), while providing adaptive system improvement recommendations that consider network limitations and the characteristics of early adolescent users. In conclusion, despite external infrastructure barriers, the LMS platform is perceived as highly positive, dependable, and motivating by students because users can distinguish external network constraints from the intrinsic quality of the application.